The Effect of Increasing Running Speed on Kinetic Ratio of Lower Limbs in Closed Kinetic Chain - Negin Soltani; Razieh Yousefian Molla; Ali Fatahi (Biyumikānīk-i varzishī, 2022)
Objective: The aim of this study was to investigate the effect of increasing running speed on motor ‎chain and kinetic ratio of lower limb joints‎. Methods: The statistical population of this study consisted of healthy people and ordinary runners. A ‎group of 28 healthy male subjects, including runners who ran more than 20 km per week, ‎were selected via convenience sampling method as research sample. They were also fully ‎acquainted with running on a treadmill. Three-dimensional kinetics parameters of the lower ‎limb joints, hip, knee, and ankle, torque and the kinetic ratio of the minimum, maximum and mean values of these ‎joints at three different speeds 2/5,3/5 and 4/5 was measured by two important instruments, ‎the camera and the force plate. Shapiro-wilks test was used to check the normality of data ‎distribution and data analysis was performed using analysis of variance with repeated ‎measurements or repeated measure through SPSS software, version 22‎. Results: Based on the results obtained in this study, the torque ratio of hip to knee and thigh to ankle ‎joints was not significant in any of the anatomical plates and axes at three speeds (p≥0.05). ‎Also, the ratio of torque of knee joints to ankle in three speeds and three planes did not ‎show a significant difference ( p≥0.05)‎. Conclusion: According to the results obtained in this study, it seems that with the knowledge of the ‎moment changes of the lower limb joints, practical solutions can be provided to reduce the ‎amount of damage when running, especially on a treadmill, to these 3 joints. ‎